Case studies of the human critical success factors in information technology (IT) implementation in Malaysian construction industry - Aziz, N.M.; Salleh, H. (Penerbit UKM, 2014)
Incorporating information technology (IT) into the business process becomes the major concern of every industry around the world. Unfortunately, the high failure rates of IT implementation revealed by researches became a serious concern to all. Much has been written about the critical success factors (CSFs) for IT implementation. But none have highlighted the major reasons for the failure, which is human issue. Human are the foundation of every organization will determine the success and failure of IT implementation. More attention should be given to this issue in an effort to reduce the failure rates. In regards to this matter, this research paper identified the CSFs focusing on the human issue. Literature findings listed 21 CSFs that contribute to the success of IT implementation across industries. Four construction organizations were selected to test the existence of the factors identified. Semi-structured interviews were employed as they offer sufficient flexibility to ensure that all relevant factors are covered. Several key issues contributing to successful implementations of IT are identified. Findings reported in this research paper will benefits the construction organizations by giving them a clearer understanding on CSFs in implementing IT, maximising the probability to success and also serve as a guideline for future planning.